2017
DOI: 10.7860/jcdr/2017/20531.9493
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Malignant Hyperthermia- A Medical Emergency: A Case Report and Review of Literature

Abstract: A four-year-old female child weighing 15 kg with diagnosis of choledochal cyst was scheduled for cyst excision and Roux-en-Y Hepatico-Jejunostomy under general anaesthesia. Her preoperative routine investigations were within normal limits. Before induction of anaesthesia, her blood pressure was 100/60 mm Hg, heart rate 84 beats/min, body temperature was 36.7°C and respiratory rate was 18 breaths/minutes. Anaesthesia was induced with 20 mcg of fentanyl sevoflurane followed by 2 mg of vecuronium bromide for endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…We found that Cpd1 exhibits good solubility (849 ± 58 µg/mL) in normal saline, which is 34-fold higher compared to dantrolene (25.7 ± 2.1 µg/mL) (Table 1 ). This enables continuous administration of the drug by infusion using the intravenous route and expands usage of the drug before and after surgery for prevention of MH and postoperative MH 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that Cpd1 exhibits good solubility (849 ± 58 µg/mL) in normal saline, which is 34-fold higher compared to dantrolene (25.7 ± 2.1 µg/mL) (Table 1 ). This enables continuous administration of the drug by infusion using the intravenous route and expands usage of the drug before and after surgery for prevention of MH and postoperative MH 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a case of postoperative MH in a child, who died from unavailability of dantrolene, was reported recently. The only symptoms in that case were tachypnea and hyperthermia [8]. In our case, uncontrolled postoperative hyperthermia was an initial sign.…”
Section: Discussionmentioning
confidence: 47%
“…We found that Compound 1 exhibits good solubility (~1 mg/mL) in normal saline, which is threefold higher compared to dantrolene in water (Extended Data Table 1). This enables continuous administration of the drug by infusion using the intravenous route and expands usage of the drug before and after surgery for prevention of MH and postoperative MH 42 .…”
Section: Pharmacokineticsmentioning
confidence: 99%